Factors associated with life quality, sleep quality, and depression in systemic sclerosis patients: a cross-sectional study from Iran - Dena Mohamadzadeh; Shirin Assar; Zhovan Fatahi; Faraneh Farsad (Reumatismo)
Objective. This study aimed to determine the prevalence and associated factors of depressive symptoms, poor sleep, and life quality among patients with systemic sclerosis (SSc).